Cost-effectiveness and Incidence of Renewable Energy Promotion in Germany - Böhringer, Christoph; Landis, Florian; Tovar Reaños, Miguel Angel (University of Oldenburg, Department of Economics, 2016)
Over the last decade Germany has boosted renewable energy in power production by means of massive subsidies. The ip side are very high electricity prices which raises concerns that the transition cost towards a renewable energy system will be mainly borne by poor households. In this paper, we combine computable general equilibrium and microsimulation analysis to investigate the cost-e ectiveness and incidence of Germany's renewable energy promotion. We nd that the regressive e ects of renewable energy promotion could be attenuated by alternative subsidy nancing mechanisms which achieve the same level of electricity generation from renewable energy sources.